2015
DOI: 10.1371/journal.pone.0124012
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Health Care Delivery and Hospital Outcomes between Non-Saudis and Saudi Nationals Presenting with Acute Coronary Syndromes in Saudi Arabia

Abstract: BackgroundSaudi Arabia has a non-Saudi workers population. We investigated the differences and similarities of expatriate non-Saudi patients (NS) and Saudi nationals (SN) presenting with acute coronary syndromes (ACS) with respect to therapies and clinical outcomes.MethodsThe study evaluated 2031 of the 5055 ACS patients enrolled in the Saudi Project for Assessment of Acute Coronary Syndrome (SPACE) from 2005 to 2007. Propensity score matching and logistic regression analysis were performed to account for majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
(17 reference statements)
3
12
1
Order By: Relevance
“…Our finding of a longer S2DT within the Australian migrant population has not previously been reported but is consistent with international reports of pre‐hospital delays in migrants and minority ethnic groups . Compared to studies by Al‐Faleh (median S2DT difference of 45 min), Lee (median difference 54 min) and Ting (median difference 60 min), our difference of 11 min is modest at best and of questionable clinical relevance. Over the past decade, the National Heart Foundation of Australia has undertaken sustained and ongoing public health campaigns targeting public awareness of cardiovascular symptoms, and these efforts have likely helped to minimise pre‐hospital delays and should be continued.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our finding of a longer S2DT within the Australian migrant population has not previously been reported but is consistent with international reports of pre‐hospital delays in migrants and minority ethnic groups . Compared to studies by Al‐Faleh (median S2DT difference of 45 min), Lee (median difference 54 min) and Ting (median difference 60 min), our difference of 11 min is modest at best and of questionable clinical relevance. Over the past decade, the National Heart Foundation of Australia has undertaken sustained and ongoing public health campaigns targeting public awareness of cardiovascular symptoms, and these efforts have likely helped to minimise pre‐hospital delays and should be continued.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies conducted in Europe, Singapore and the Middle East have also documented significantly higher rates of complications and mortality between migrant patients and those from a minority background . These findings contrast large studies conducted in the United States, which observed no significant differences in length of hospital stay, adverse events or in‐hospital mortality between patients of different ethnic backgrounds …”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations